Applying bayesian networks to injury occurrence in professional football - Yung, K. K.-Y.; Wu, P. P.-Y.; Ardern, C.; Tröß, T.; Hadji, A.; Fünten, K.; Hecksteden, A.; Serpiello, F.; Robertson, S. (British Journal of Sports Medicine, 2021)
Background Bayesian networks (BN) are directed acyclic graphs derived from empirical data that describe the dependency and probability structure. It may facilitate understanding of complex epidemiology by presenting the data in a multi-dimensional visual representation, and guiding inferences on the likelihood of the severity based on new information.